Warnman dictionary 2010 - Burgman, Albert; Cadigan, John.; Wangka Maya Pilbara Aboriginal Language Centre (South Hedland, W.A. : Wangka Maya Pilbara Aboriginal Language Centre, 2010)
Annotation pending.
Previous ed. 2003.
Keywords: Warnman language -- Dictionaries -- English language; English language -- Dictionaries -- Warnman language; Aboriginal Australians -- Western Australia -- Pilbara -- Languages; Warnman language (A62) (WA SF51-11); Language - Vocabulary - Word lists; Language - Vocabulary - Dictionaries and glossaries; Australian